A Reminder of the Anatomy of the Recurrent Artery of Heubner - ÖZDOĞMUŞ, NECMETTİN ÖMER (GEORG THIEME VERLAG KG, 2009)
Previous accounts of the recurrent artery of Heubner show serious inconsistencies concerning the origins, dimensions and numbers of the artery. In the present study, based on 54 (38 male, 16 female) human autopsy brains the common type of the recurrent artery of Heubner was present bilaterally in 46 cases (85.2 %), while in 6 (11.1 %) cases it was present only on one side (4 on the right, 2 on the left). Unilateral vessels were seen only in the male autopsy brains. The recurrent artery of Heubner could not be identified in 2 brains (3.7 %). Multiple Heubner arteries were not observed in the present study. No gender differences were observed regarding the origin and dimensions of the recurrent artery of Heubner. 76 recurrent arteries of Heubner arising from the junction of the anterior cerebral artery (ACA) and anterior communicating artery (ACoA) (79.2 %) had a mean diameter of 0.66 +/- 0.11 mm. In 14 arteries the artery derived from the A2 segment of the ACA (14.6 %) and the mean diameter was 0.66 +/- 0.17 mm; in 6 arteries it originated from the A1 segment of the ACA (6.2 %) and the mean diameter was 0.47 +/- 0.15 mm. The average diameter was calculated as 0.67 +/- 0.12 mm and ranged between 0.40 and 0.90 mm, irrespective of sex or side. A detailed anatomical knowledge of the recurrent artery of Heubner is important when considering vascular surgery in this area.
Keywords: recurrent artery of Heubner; outer diameter; origin; anterior cerebral artery; anterior communicating artery; ANTERIOR CEREBRAL-ARTERY; MICROSURGICAL ANATOMY; ANEURYSMS; INFARCTS; COMPLEX